ESTABLISHMENT OF INTRAPERITONEAL TRANSPLANTATION MODEL OF CISPLATIN-RESISTANT OVARIAN CARCINOMA CELL IN SCID MICE - 张辉 赵群 左连富 王晓玲 王永军 贾金华 康山 (Chinese journal of cancer research, 2006)
Objective： to develop an intraperitoneal transplantation model of human ovarian carcinoma SKOV3/CDDP cell in severe combined immunodeficiency （SCID） mouse and to study its biologic characteristics. Methods： Sixteen qualified C.B 17/SCID mouse were divided into two groups randomly. Human ovarian carcinoma SKOV3 or SKOV3/CDDP cells were injected intraperitoneally into the SCID mouse at the amount of 1×10^7 cells （0.5 mL） per mouse. The behaviors of mice, tumor growth and morphology were analyzed. The expression of cancer antigen 125 （CA125）, GST-π and Topo-Ⅱ were examined by immunohistochemical method. Results： In this experimental study, transplanted tumors are formed in 100% SCID mice in the two groups. The morphology, growth pattern and CA125 secretion of SKOV3/CDDP group were as same as those of SKOV3 group. It shows that the tumors of the two groups kept the characteristics of ovaries serosity papillary adenocarcinoma. Compared with SKOV3 group, the expression of GST-π and Topo-Ⅱ gene in SKOV3/CDDP group were significantly higher （P〈0.05）. Conclusion： An intraperitoneal transplantation model of human ovarian carcinoma SKOV3/CDDP in SCID mice has been developed successfully. It may be an ideal animal model for biotherapy research of ovarian carcinoma as it can simulate the biological behavior of peritoneal metastasis of human ovarian carcinoma and the drug tolerance is maintained.